DETERMINANTS OF BREAST-SELF EXAMINATION (BSE) BEHAVIOR IN STUDENTS - Astuty, Delfriana Ayu; M.A, Irwan S, (Universitas Aisyah Pringsewu, 2025)
Behavior is a collection of various factors that interact with each other. We often don't realize that these interactions are so complex that sometimes we don't have time to think about why someone is implementing a certain behavior. Therefore, it is very important to be able to examine the reasons behind an individual's behavior before he is able to change that behavior. Breast Self Examination (BSE) or in Indonesian this term is a synonym for BSE, namely, breast self-examination to find abnormal lumps in the breast. BSE does not require costs and provides benefits to women in increasing their knowledge and ability to do so. Breast cancer (carcinoma mammae) is a malignancy that originates from breast tissue, both from the ductal epithelium and the lobules. Mammary Carcinoma occurs due to the condition of cells that have lost their normal control and mechanisms, so they experience abnormal, fast and uncontrolled growth. This type of research is an analytical survey with a cross sectional approach. The location of this research is at UIN North Sumatra Medan. The time of this research starts from August to October 2023. The respondents of this research are all female students who are currently in semesters 3, 5 and 7. The number of samples in this research was 528 people with a sampling technique namely Accidental Sampling . Based on the results of bivariate analysis using Chi-Square, the most determinant of BSE behavior in female students is the respondent's knowledge with peer support, then BSE actions with the support of health workers, and BSE actions with peer support. Based on the results of MANOVA analysis using the Krusall Wallis Test, the most determinant behavior in BSE actions among students is peer support and support from health workers. Based on MANOVA analysis using the Krusall Wallis Test, of the four behavioral components, only the information exposure variable has a relationship with female students' perceptions about preventing disease according to Islam. The results of this research can be used as learning material and input for respondents to increase their concern for their own health while also paying attention to the health of the people around them. Keywords; Behavior, Breast Self Examination, Carcinoma Mammary